Historical Development, Social Structure, and Cultural Preservation in Marindal 1 Village - Oktavianti Hutabarat; Ekel Thory Rafael Ginting; Fani Anjani; Atikah Rahmi (Warisan: Journal of History and Cultural Heritage, 2026)
Marindal 1 Village in Patumbak District, Deli Serdang Regency, North Sumatra, possesses a long historical trajectory characterized by social diversity and enduring cultural traditions. Although previous studies have documented aspects of local history and culture, limited attention has been devoted to examining the interrelationship between historical development, social structure, and cultural preservation within a unified analytical framework. This study investigates the historical development of Marindal 1 Village, its social structure, and the preservation of its cultural heritage. The research employs a qualitative historical approach using the historical method, encompassing heuristics, source criticism, interpretation, and historiography, supported by an extensive literature review to reconstruct historical continuity and explain socio-cultural dynamics through documented evidence. The findings indicate that the village developed through sustained interaction among Batak, Malay, and Javanese communities since the nineteenth century, giving rise to a social structure characterized by kinship, cooperation, and collective solidarity. These social values have enabled the continuous preservation and adaptation of local traditions despite the pressures of urbanization and globalization. This study contributes to local history scholarship by demonstrating how historical development has shaped social structure and strengthened cultural preservation, providing a comprehensive understanding of rural socio-cultural continuity in Marindal 1 Village.